Negotiating privacy. Athletes` assessment and knowledge of the ADAMS - Scharf, M.; Zurawski, N.; Ruthenberg, T. (Performance Enhancement & Health, 2018)
Elite athletes must comply with a complex system of controls in order to participate in international sports and competitions. The Anti-Doping Analysis Management System (ADAMS) is one of the control devices that subject athletes to a regime of control and surveillance. Anti-doping organisations (ADOs) and national and international sports federations, for example, make use of their whereabouts data for test planning and decision-making regarding test routines. Athletes` participation is mandatory, otherwise they cannot take part in competitive sports. This, in return, means that they agree to have their privacy and that of others compromised. Thus, a tension exists between the fight against doping and the integrity of privacy. Through a qualitative study on doping, controls and control practices we have learned that athletes view ADAMS as a necessary nuisance, but we do not know what they actually know about the system. We conducted a survey among German elite athletes (summer and fall 2016) to further explore the usage routines of ADAMS, the athletes` knowledge of the tool and their assessment of possible privacy infringements. A total of 523 German athletes registered in the Registered Testing Pool and National Testing Pool (N = 2,152) of the National Anti-Doping Agency of Germany, who provided us with a representative sample, took part. We found from the survey that athletes have rather contradictory views concerning ADAMS, and often little knowledge of the system as such and would (or know how to) engage in playing the system to avoid controls. Athletes generally voice strong feelings about privacy, while simultaneously accepting ADAMS despite the concerns raised. However, they want more transparency regarding the system and the fight against doping. We conclude our analysis with a discussion of ADAMS as a surveillance system that, by storing, processing and using data for the purpose of anti-doping measures, engages in social sorting among athletes and creates what we call spillover effects and apparent power asymmetries that have been established throughout the system. We argue for a new balance within the system of controls, in which athletes are to be treated as actors, i.e. equal stakeholders who take part in decision-making regarding the system, rather than simply users and clients of a control interface. It seems that ADAMS threatens athletes` privacy and that of their social environment rather than guaranteeing fairness for them.